2017
DOI: 10.3390/agriculture7050041
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Nutrient Load Changes from Fertilizer Application Scenarios in Six Catchments around the Baltic Sea

Abstract: Abstract:The main environmental stressor of the Baltic Sea is elevated riverine nutrient loads, mainly originating from diffuse agricultural sources. Agricultural practices, intensities, and nutrient losses vary across the Baltic Sea drainage basin (1.75 × 10 6 km 2 , 14 countries and 85 million inhabitants). Six "Soil and Water Assessment Tool" (SWAT) models were set up for catchments representing the major agricultural systems, and covering the different climate gradients in the Baltic Sea drainage basin. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Only a limited number of studies on nutrient loads have analysed climate impacts combined with comprehensive socioeconomic changes. Most impact studies in the Baltic Sea Drainage Basin (BSDB) evaluated effects of nutrient reduction measures or land use changes (Wulff et al 2014; Thodsen et al 2017). Andersson and Arheimer (2003) made a historical reconstruction of nutrient pathways during 100 years of societal changes in a Swedish river basin, while Eriksson Hägg et al (2014) combined climate projections to the 2100s with scenarios of changes in population and their diet in the BSDB.…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited number of studies on nutrient loads have analysed climate impacts combined with comprehensive socioeconomic changes. Most impact studies in the Baltic Sea Drainage Basin (BSDB) evaluated effects of nutrient reduction measures or land use changes (Wulff et al 2014; Thodsen et al 2017). Andersson and Arheimer (2003) made a historical reconstruction of nutrient pathways during 100 years of societal changes in a Swedish river basin, while Eriksson Hägg et al (2014) combined climate projections to the 2100s with scenarios of changes in population and their diet in the BSDB.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling of groundwater model with SWAT hydrological model to obtain detailed information on groundwater recharge rate and nitrate loads leached from soil. SWAT has already been used in a number of studies on the hydrological balance and nutrient transport in the Baltic region [38][39][40][41][42][43], including the Puck Bay region [44,45]. However, there has been no attempt to apply SWAT-MODFLOW coupling on the Polish Baltic coast.…”
mentioning
confidence: 99%
“…Although unable to differentiate the extent of fertilizer N runoff from other nutrient sources, Asmala et al [134] suggested that the best approach to reduce nutrient flows was to improve fertilizer use efficiency at the farm level. By performing simulations with SWAT model for six catchments with major agricultural crop production systems in the Baltic Sea drainage basin, Thodsen et al [135] estimated that a change in mineral fertilizer use of ± 20% increased watershed nitrate-N loads between 0 and ± 13%.…”
Section: The Baltic Seamentioning
confidence: 99%